Programme notes Software gives Alan Gillard the chance to show green benefits. - Gillard, Alan (RIBA Journal, 2008)
The article presents a case study of an environmental design student who investigates the application of interseasonal heat storage in small buildings in Cardiff, Wales. He was convinced of the benefit from using building performance analysis software. The software allowed him to show how an investment in sustainable design will pay off in the future such as in the reduction of energy bills for heating, cooling and lighting.